2000
DOI: 10.1161/01.res.86.8.871
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Gap Junctional Coupling in Hypertrophied Right Ventricles of Rats With Monocrotaline-Induced Pulmonary Hypertension

Abstract: The present study investigates the remodeling of gap junctional organization in relation to changes in anisotropic conduction properties in hypertrophied right ventricles (RVs) of rats with monocrotaline (MCT)-induced pulmonary hypertension. In contrast to controls that showed immunolocalization of connexin43 (Cx43) labeling largely confined to the intercalated disks, RV myocytes from MCT-treated rats showed dispersion of Cx43 labeling over the entire cell surface. The disorganization of Cx43 labeling became m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
93
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 27 publications
11
93
2
1
Order By: Relevance
“…In a partial contrast with previous studies of connexin43 changes in HF (Dupont et al, 2001;Emdad et al, 2001;Uzzaman et al, 2000), we found only mild difference in total connexin43 levels by immunohistochemistry (but there was over 60% reduction by Western blot), and the changes in localization were also insignificant. Possible reason for this discrepancy can be differences in HF models or methods used.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In a partial contrast with previous studies of connexin43 changes in HF (Dupont et al, 2001;Emdad et al, 2001;Uzzaman et al, 2000), we found only mild difference in total connexin43 levels by immunohistochemistry (but there was over 60% reduction by Western blot), and the changes in localization were also insignificant. Possible reason for this discrepancy can be differences in HF models or methods used.…”
Section: Discussioncontrasting
confidence: 99%
“…Some of the previous studies demonstrated a reduction in connexin43 levels in left ventricles of transplant patients with endstage HF (Dupont et al, 2001). Lateralization of connexin43 from intercalated discs to lateral membrane of myocytes occurs in experimentally induced hypertrophy of right and left ventricle of the rat (Uzzaman et al, 2000;Emdad et al, 2001). Apart from alterations in connexin43 levels, the dephosphorylation of connexin43 was described during several pathological states, including myocardial ischemia (Beardslee et al, 2000;Burstein et al, 2009).…”
mentioning
confidence: 99%
“…One indicator of this stress was the increase in the expression of ␤-MHC, the fetal form of myosin in the mouse (27,28). This is an energy conservation switch as ␤-MHC has a lower ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that RV hypertrophy is associated with both disorganization of gap junction distribution and alteration of anisotropic conduction properties (28,29). Consequently, hypertrophic remodeling might induce electromechanical coupling alteration during PHT-induced RV dysfunction (29).…”
mentioning
confidence: 99%